Prediction of zeta potential behavior of minerals using column flotation technique - Caraga, Chaitanya S. (College of Engineering, University of the Philippines Diliman, 2015)
This study aims to determine the zeta-potential of pure minerals Titania, TiO2, and Hematite, Fe2O3, using the known zeta-potentials of air bubbles in aqueous media as a function of pH and electrolyte concentration. In the bubble-particle collection, attachment is conducted through column flotation technique. Column flotation of each mineral is performed for 5 minutes for pH 3 to 11 and at electrolyte concentrations 0.01 M, 0.001 M and 0.0001 M KNO3. The concentration of attached particles onto bubbles is measured using UV-VIS Spectrophotometry. From the attached fractions of minerals to bubbles, the iso-electric points of TiO2 and Fe2O3 are determined at pH ranges 3.5 to 4.5 and pH 5 to 7, respectively. The modified Boltzmann equation is used to calculate and approximate the magnitude of the zeta potentials of TiO2 and Fe2O3 in aqueous environment. The results showed that as the electrolyte concentration increases, the magnitude of zeta-potential decreases. The isoelectric point, signs and magnitude of zeta potentials determined by column flotation are validated by the measurements of Zeta-Meter 4.0. For one-component systems interaction, a) TiO2- TiO2 particles are stable at conditions greater than pH 9, and unstable at conditions below pH 8; b) Fe2O3- Fe2O3 particles are stable at pH 3 to 4 and pH 9 to 11 and unstable at pH 5 to 8; c) Bubble- Bubble interaction are unstable at pH 3 to 5 and stable at pH 6 to pH 11. For two-component systems, a) Bubble-TiO2 particle interactions showed that attractive forces dominated at pH 3-5 and repulsive forces at pH 6 to 11. For the case of the Bubble- Fe2O3 particle interactions, attraction prevailed at pH 3 to 6 and repulsion at pH 7 to 11. The inter-particle behavior of minerals and bubbles are analyzed using the classical DLVO (Derjaguin, Verway, Landau and Overbeek) theory.